Digital marketing fundamentals from strategy to ROI - Visser, Marjolein; Sikkenga, Berend; Berry, Mike 1958-
Digital Marketing Fundamentals is the first comprehensive digital marketing textbook to cover the entire marketing process. The academic theory behind Digital Marketing, as well as techniques and media, isdiscussed. Digital Marketing Fundamentals is easy to read and contains many international examples and cases. The Dutch version of this book (Basisboek Online Marketing) has become a standard issue in The Netherlands. In this book, all relevant aspects of digital marketing are addressed: strategic aspects, the use of the Internet for market research, product development and realisation, branding, customer acquisition, customer loyalty and order processing. The book also discusses effective websites and apps, digital analytics and planning, and management. The application of social media and mobile communications is seamlessly integrated into the topics. Digital Marketing Fundamentals is suitable for commercial and management courses in higher education, including universities and business schools, and for professionals working in digital marketing. To request access to the book's online resources, please click here: http://www.digitalmarketing.noordhoff.nl For FAQs: https://www.basisboek-onlinemarketing.nl/faq-lecturers.html
JMA Acopiado (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
aMarjolein Visser is Managing Consultant of MarketWise and founder of TourWise. Berend Sikkenga is Head of eCommerce at LEGO. Mike Berry is a Digital Marketing consultant, trainer and Professor of Practice at Hult International Business School, USA.
Keywords: Internet marketing; Marketing -- Management